The influence of scar on the spatio-temporal relationship between electrical and mechanical activation in heart failure patients - Maffessanti, Francesco; Jadczyk, Tomasz; Kurzelowski, Radosław; Regoli, François; Caputo, Maria Luce; Conte, Giulio; Gołba, Krzysztof S; Biernat, Jolanta; Wilczek, Jacek; Dąbrowska, Magdalena; Pezzuto, Simone; Moccetti, Tiziano; et al. (Europace, 2020)
AIMS: The aim of this study was to determine the relationship between electrical and mechanical activation in heart failure (HF) patients and whether electromechanical coupling is affected by scar. METHODS AND RESULTS: Seventy HF patients referred for cardiac resynchronization therapy or biological therapy underwent endocardial anatomo-electromechanical mapping (AEMM) and delayed-enhancement magnetic resonance (CMR) scans. Area strain and activation times were derived from AEMM data, allowing to correlate mechanical and electrical activation in time and space with unprecedented accuracy. Special attention was paid to the effect of presence of CMR-evidenced scar. Patients were divided into a scar (n = 43) and a non-scar group (n-27). Correlation between time of electrical and mechanical activation was stronger in the non-scar compared to the scar group [R = 0.84 (0.72-0.89) vs. 0.74 (0.52-0.88), respectively; P = 0.01]. The overlap between latest electrical and mechanical activation areas was larger in the absence than in presence of scar [72% (54-81) vs. 56% (36-73), respectively; P = 0.02], with smaller distance between the centroids of the two regions [10.7 (4.9-17.4) vs. 20.3 (6.9-29.4) % of left ventricular radius, P = 0.02]. CONCLUSION: Scar decreases the association between electrical and mechanical activation, even when scar is remote from late activated regions.
Keywords: magnetická rezonance kinematografická; Left bundle branch block; Cardiac Resynchronization Therapy; Cardiac resynchronization therapy; srdeční resynchronizační terapie; Cardiac magnetic resonance; Magnetic Resonance Imaging, Cine; Humans; srdeční komory; jizva; Scar; Heart failure; Heart Failure; Heart Ventricles; Cicatrix; lidé; Activation; srdeční selhání